Comprehensive Physiology 1999
DOI: 10.1002/cphy.cp070521
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐Like Growth Factor I Actions on Somatic Growth

Abstract: The sections in this article are: Indirect Evidence that Insulin‐Like Growth Factor I Participates in the Regulation of Somatic Growth Clinical: Correlations Between Growth and Insulin‐Like Growth Factor I Levels in Serum Experimental: Growth Hormone‐Dependent Regulation of Insulin‐Like Growth Factor I m RNA and Protein Expression in Various Tissues and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 191 publications
1
12
0
Order By: Relevance
“…The IGF-I hormone plays a crucial role in the postnatal linear growth of animals (e.g. Yakar et al, 2002;Zapf and Froesch, 1999). In this study an association of the IGF-I gene polymorphism with body size traits and subjective assessment of body muscle and fat class in Coloured Polish Merino sheep was investigated; however, the effects of IGF-I genotypes on these traits were not significant.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The IGF-I hormone plays a crucial role in the postnatal linear growth of animals (e.g. Yakar et al, 2002;Zapf and Froesch, 1999). In this study an association of the IGF-I gene polymorphism with body size traits and subjective assessment of body muscle and fat class in Coloured Polish Merino sheep was investigated; however, the effects of IGF-I genotypes on these traits were not significant.…”
Section: Discussionmentioning
confidence: 81%
“…Circulating IGF-I concentration has an impact on fetal and neonatal size and postnatal growth in several species (Baker et al, 1993;Breier et al, 1988;Duclos et al, 1999;Yakar et al, 2002;Zapf and Froesch, 1999) Szewczuk et al (2013) reported effects of two SNPs in the IGF-I gene on body weight in the second month of life in calves and average daily gains in the periods from the first to the second months and from the second to the third months of life and for the whole rearing period. Zhang et al (2008) investigated polymorphism of the IGF-I gene and its association with growth and body size traits in Nanjiang Huang goats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IGF1 gene may play important roles in growth of multiple tissues, including muscle cells (myocyte differentiation cell multiplication), cartilage (chondrocyte colony formation, alkaline phosphatase activity) and bone (osteoblast division and proliferation) (Zapf and Froesch, 1999). Intense genetic selection of broilers has successfully increased growth rate and breast muscle percentage.…”
Section: Introductionmentioning
confidence: 99%
“…IGF-I has an important role in growth of fetal organs and skeletal muscles (Lok et al, 1996). IGF-I is considered as a key factor in animal growth through its effect on longitudinal bone growth, muscle growth and cartilage growth (Duclos et al, 1999;Zapf and Froesch, 1999;Yakar et al, 2002). IGF-1 plays an important role in mammalian fertility through the regulation of many hormones which are critical for reproductive system (Miller and Gore, 2001;Velazquez et al, 2008).…”
Section: Resultsmentioning
confidence: 99%